Empowering ESP Students Through a Scientific Approach: Unveiling the Impact on Engagement and Reading Comprehension Achievement - Ismitasari, Elisa; Ruminda, Ruminda; Bachtiar, Bachtiar (Universitas Pahlawan Tuanku Tambusai, 2024)
This study is anchored in the constructivist theoretical perspective, which emphasizes the active role of learners in constructing knowledge through interaction and experience. It aims to investigate the efficacy of a scientific method in improving reading comprehension and student engagement among Informatics Study Program students at Universitas Jenderal Achmad Yani Cimahi, Indonesia. The study utilizes a mixed-methods research design to assess the effectiveness of traditional lecture methods and the scientific approach in enhancing reading achievement. The study was conducted at Universitas Jenderal Achmad Yani Cimahi in West Java and involved 68 second-semester students enrolled in the Informatics Study Program, with a specific focus on the English Practicum course. The results of the research found that the scientific approach led to better reading comprehension and higher engagement levels compared to traditional lectures. However, when comparing the two methods, the statistical analysis showed no significant difference between them, suggesting that the impact of the scientific approach may vary. The study also found the value of student-centered, evidence-based teaching methods for improving educational outcomes in English for Specific Purposes (ESP) settings. The study emphasizes the necessity of employing adaptable, empirically supported teaching methods to address a wide range of learning requirements and enhance educational achievements. Although the study has limitations that are specific to its environment and relies on data provided by the participants themselves, the findings strongly support a wider adoption of scientific approaches in teaching reading comprehension.